(untitled) (Shaheed Smriti Journal, 2025)
This study examined how a teacher’s philosophy of teaching influences the learning achievement of undergraduate mathematics students. Using a reflective qualitative review design, the study analyzed data drawn from existing scholarly literature related to teachers’ beliefs, instructional practices, and student learning outcomes. The review found that teachers’ philosophical orientations toward reality, knowledge, values, and pedagogy significantly shaped classroom practices, with student-centered, inclusive, and reflective approaches consistently improving student engagement, understanding, and problem-solving skills in mathematics. The study also identified challenges such as low academic achievement, learner diversity, and rapid technological change. Evidence from recent studies on online learning, problem-posing strategies, and AI literacy highlighted the importance of teachers’ philosophical clarity and continuous self-reflection. The study concludes that institutions should support reflective practice, curriculum innovation, and equitable learning opportunities to enhance undergraduate mathematics education.